Inside the Mandapa of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is a sculpture of a female on the south-facing (inner) side of the pillar in the northwest corner of the mandapa (pillared hall) of the Suswani Mata Temple. It is said that there used to be an inscription below this sculpture which is probably not visible now because of the later added paint. This inscription was supposed to be the sole epigraphical evidence dating the construction of the temple in the 10th century CE. A sculpture carved in deep relief (probably a female) is shown sitting on a pedestal. The sculpture is two-handed only and is shown wearing a mukuta (crown).